(untitled) (Conference on English Language Teaching, 2023)
Reading is an important skill that has many benefits. However, since English is a foreign language, many students get difficulties in reading. To increase students’ reading skill, teachers should apply an effective and interesting media. The use of technology as a teaching medium is expected to be able to increase the students’ interest and skill. One of the technologies that can be used for teaching reading is Google Classroom. Therefore, this article aims at investigating the effect of using Google classroom in teaching reading for junior high school students. This research used quasi-experimental design. Two classes of seventh-grade students in Kediri participated in this research. The data was gathered by using tests: pre-test and post-test. Then to test the hypothesis, ANCOVA was used. This research found that the mean score for control group was 49.12 (pre-test) and 76.16 (post-test). The mean score for experimental group was 48.15 (pre-test) and 81.69 (post-test). From the data analysis using ANCOVA, the result of significant value is smaller than the significant level (0.001 < 0.05. It means that H0 was rejected. It can be concluded that using Google Classroom is effective in teaching reading for junior high school students.